Agricultural Gross Domestic Product and Farmer Exchange Rate on Income Distribution Inequality on the Island of Sumatra - Yahdiyani, Rafiqa; Hermanto, Bambang Agoes; Fauziah, Dien Ajeng (Formosa Journal of Applied Sciences, 2024)
This study examines the relationship between agricultural gross domestic product (GDP) and farmer exchange rate on income distribution inequality on the island of Sumatra. This research employs descriptive research methods with a quantitative approach, utilizing secondary data in the form of time series data from 2013 to 2022 (ten years) and cross-sectional data from ten provinces on the island of Sumatra obtained from the Central Statistics Agency (BPS). Descriptive statistical analysis and panel data regression were conducted using the Eviews 13 software. The findings of the research indicate that the agricultural sector GRDP variable exerts a significant negative effect on income distribution inequality, the Farmer Exchange Rate has no effect on income distribution inequality in the provinces of Sumatra Island between 2013 and 2022.